1994
DOI: 10.1139/g94-087
|View full text |Cite
|
Sign up to set email alerts
|

Genomic in situ hybridization differentiates between A/D- and C-genome chromatin and detects intergenomic translocations in polyploid oat species (genus Avena)

Abstract: The genomic in situ hybridization (GISH) technique was used to discriminate between chromosomes of the C genome and those of the A and A/D genomes in allopolyploid oat species (genus Avena). Total biotinylated DNA from A. strigosa (2n = 2x = 14, AsAs genome) was mixed with sheared, unlabelled total DNA from A. eriantha (2n = 2x = 14, CpCp) at a ratio of 1:200 (labelled to unlabelled). The resulting hybridization pattern consisted of 28 mostly labelled and 14 mostly unlabelled chromosomes in the hexaploids. Att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
108
1
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(137 citation statements)
references
References 0 publications
22
108
1
2
Order By: Relevance
“…A number of authors have attempted to identify individual C-genome chromosomes in hexaploid oats by GISH and FISH (e.g. Chen and Armstrong, 1994;Jellen et al, 1994;Leggett and Markhand, 1995;Yang et al, 1999). Fominaya et al (1995) and Linares et al (1996) performed FISH analysis using a repeated DNA sequence (pAm1) specific to C-genome chromosomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of authors have attempted to identify individual C-genome chromosomes in hexaploid oats by GISH and FISH (e.g. Chen and Armstrong, 1994;Jellen et al, 1994;Leggett and Markhand, 1995;Yang et al, 1999). Fominaya et al (1995) and Linares et al (1996) performed FISH analysis using a repeated DNA sequence (pAm1) specific to C-genome chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…At the moment, the GISH was unable to separate the A-and D-genome chromosomes in hexaploid oats. But absolute discrimination between A/D-and C-genome chromosomes has been demonstrated by several oat workers (Jellen et al, 1994;Chen and Armstrong, 1994;Leggett and Markhand, 1995;Yang et al, 1999). These authors observed small C-genome segments translocated onto A-or D-genome chromosomes (abbreviated as C-A/D translocation) and vice versa (abbreviated as A/D-C) for A-or D-segments translocated onto C-genome chromosomes.…”
Section: Introductionmentioning
confidence: 99%
“…The D genome of the hexaploids is considered to have substantial similarities with the A genome based on GISH results (Chen and Armstrong, 1994;Jellen et al, 1994;Hayasaki et al, 2000). On the other hand, discrimination of the closely related A and D genomes is possible using an A genomespecific AS120a sequence (Linares et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Through the use of chromosome-specific fluorescent in situ hybridi-zation (FISH) markers, at least nine reciprocal translocations have been detected in tetraploid Nicotiana tabacum, confirming that most tobacco chromosomes are associated with one of the two parental genomes [88]. Based on whole-genome in situ hybridization analysis, five reciprocal translocations have been found within the tetraploid Avena sativa genome, with as many as 18 detected in hexaploid Avena sativa [89]. Using FISH and other methods, we have confirmed the genetic parentage of 4nAT and verified the heterologous hybrid nature of these allotetraploid fish [1].…”
Section: Phenotypic and Genotypic Variation Of 4nat Lineagesmentioning
confidence: 92%